25 Years of the World Health Organisation Collaborating Centre for Nursing in Brazil: A Historical–Social Research. (7th December 2015) - Mendes, Isabel A.; Ventura, Carla A.; Trevizan, Maria A.; Marchi‐Alves, Leila M.; Gazzotti, Juliana; Tognoli, Silvia H.; Pasqualin, Líviade O.
Abstract : The aim of this study was to analyse the development of the World Health Organization (WHO) Collaborating Centre for Nursing in Brazil in view of the evolution in its Terms of Reference. The timeframe considered ranged from 1986 to 2013. A work plan was elaborated, which included the identification, location and analysis of primary sources, with a view to interpreting the facts based on the designation proposal, the approved Terms of Reference and the annual reports. The 25‐year development of the WHO Collaborating Centre for Nursing in Brazil demonstrates its evolution as an open system that attempts to adapt to external requirements while considering its internal characteristics and peculiarities. The Collaborating Centre's actions were focused on distinction and on increasing integration processes, based on information feedback and internal and external control flows. The WHO Collaborating Centre for Nursing in Brazil has complied with its mission of contributing to nursing research development. Copyright © 2015 John Wiley & Sons, Ltd.